The Implementation of the ISPS Code in Indonesian Ports and its Impact on National Income - Ramadhan Hasri Harahap (Brilliant International Journal Of Management And Tourism, 2025)
This study aims to measure and analyze: (i) the impact of government policies on the implementation of the International Ship and Port Facility Security (ISPS) Code in ports on state revenue; and (ii) stakeholder expectations regarding the implementation of the ISPS Code in Indonesian ports. The research method used is a mixed methods approach, consisting of a quantitative approach using the 2021 Indonesian Input-Output Table and a qualitative approach through data analysis using NVivo software. Quantitative data was used to calculate the macroeconomic impact of ISPS Code implementation, while qualitative data was obtained from in-depth interviews with various stakeholders such as port authorities, terminal operators, shipping companies, and relevant government agencies. The results show that the implementation of the ISPS Code in Indonesian ports has made a positive contribution to the national economy. Quantitatively, there was an increase in macroeconomic indicators, including an increase in Gross Domestic Product (GDP) of 0.003%, worker income of 0.00003%, revenue from taxes minus product subsidies of 0.017%, and revenue from taxes on production subsidies of 0.002%. This improvement reflects the strategic role of the ISPS Code in strengthening port security, the smooth flow of goods, and the trust of international trading partners. Qualitatively, this study reveals that stakeholders' expectations regarding the implementation of the ISPS Code include the need for the government to address existing obstacles. These obstacles include the persistence of ports that comply with the ISPS Code administratively but not yet meet operational standards, weak coordination and synergy between institutions, the suboptimal role of port authorities, limited human resources, convoluted bureaucracy, and minimal use of advanced technology. This study recommends strengthening regulations, increasing human resource capacity, simplifying bureaucratic procedures, and adopting advanced technology to support the effective implementation of the ISPS Code in Indonesia.